Konservasi Sumber Daya pada Masyarakat Pesisir Berbasis Kearifan Lokal - Syarif, Erman; Hendra, Hendra; M, Maddatuang; Saputro, Alief (Civic Education Law and Humaniora : Jurnal Pengabdian Masyarakat Terintegrasi, 2023)
Through competent, intelligent, sustainable and long-term oriented human resources, the optimization and success of further development of natural resource management can be achieved. The PKM activities carried out combine lecture and discussion methods. This PKM activity aims to: 1) increase coastal community knowledge about resource conservation, 2) increase coastal community awareness about resource conservation, and 3) form environmentally friendly coastal community behavior. The results of the service showed that the participants' knowledge and involvement in protecting resources had increased. Coastal and marine areas must be utilized sustainably and implemented responsibly.